Reducing Human-Tsetse Contact Significantly Enhances the Efficacy of Sleeping Sickness Active Screening Campaigns: A Promising Result in the Context of Elimination. - Fabrice Courtin; Mamadou Camara; Jean-Baptiste Rayaisse; Moise Kagbadouno; Emilie Dama; Oumou Camara; Ibrahima S Traoré; Jérémi Rouamba; Moana Peylhard; Martin B Somda; Mamadou Leno; Mike J Lehane; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Control of gambiense sleeping sickness, a neglected tropical disease targeted for elimination by 2020, relies mainly on mass screening of populations at risk and treatment of cases. This strategy is however challenged by the existence of undetected reservoirs of parasites that contribute to the maintenance of transmission. In this study, performed in the Boffa disease focus of Guinea, we evaluated the value of adding vector control to medical surveys and measured its impact on disease burden. METHODS:The focus was divided into two parts (screen and treat in the western part; screen and treat plus vector control in the eastern part) separated by the Rio Pongo river. Population census and baseline entomological data were collected from the entire focus at the beginning of the study and insecticide impregnated targets were deployed on the eastern bank only. Medical surveys were performed in both areas in 2012 and 2013. FINDINGS:In the vector control area, there was an 80% decrease in tsetse density, resulting in a significant decrease of human tsetse contacts, and a decrease of disease prevalence (from 0.3% to 0.1%; p=0.01), and an almost nil incidence of new infections (<0.1%). In contrast, incidence was 10 times higher in the area without vector control (>1%, p<0.0001) with a disease prevalence increasing slightly (from 0.5 to 0.7%, p=0.34). INTERPRETATION:Combining medical and vector control was decisive in reducing T. b. gambiense transmission and in speeding up progress towards elimination. Similar strategies could be applied in other foci.